Identification of CrDCL1-mediated microRNA biogenesis in green alga Chlamydomonas reinhardtii - Sun, Ting; Tao, Ming; Di, Qinglang; Hu, Zhangli; Li, Hui; Lou, Sulin (Frontiers in Microbiology, 2025)
In eukaryotes, microRNAs (miRNAs) are generated by Dicer/Dicer-Like (DCL)-mediated cleavage. Previous studies identified three DCL genes (CrDCL1-3) in Chlamydomonas reinhardtii and indicated that CrDCL3 mediated the production of most miRNAs, while CrDCL1 protein was mainly involved in siRNA biogenesis. The role of CrDCL1 in miRNA biogenesis remains unclear. This study constructed a phylogenetic tree, performed structural analyses of Dicer/DCL proteins from multiple species and screened and verified dcl1 and dcl3 mutant strains. Using CC-5325 and dcl3 mutant as control groups, we performed sRNA-sequencing, RT-qPCR, and Northern blot verification experiments on dcl1 mutant to explore the involvement of CrDCL1 in miRNA biogenesis in C. reinhardtii. The results demonstrated that CrDCL1 was involved in the production of 22 miRNAs, including cre-miR910, novel-miR01, novel-miR03, novel-miR04, novel-miR05, and novel-miR06, whose production was depended not only on CrDCL1 but also on CrDCL3. The present findings highlight the production of some C. reinhardtii miRNAs that may be involved in multiple CrDCL proteins, which is different from animals and plants. The results of this study will enrich the knowledge of miRNA biogenesis in eukaryotes.